MUSNAD AL-IMĀM ZAID IBN ‘ALĪ: Kajian atas Autentisitas, Konfigurasi, dan Karakteristik - Mus‘idul Millah (Holistic al-Hadis, 2022)
A cross-ideological based literature review often cannot avoid bias. This will usually become more problematic when the researcher is completely at odds with the ideology of the literature being studied. This article will try to examine the Musnad al-Imām Zaid ibn 'Alī which comes from the Shi'a Zaidiah circle descriptively, regarding its authenticity, configuration, and characteristics. This work is still not getting enough attention. Although several figures have reviewed this book, the ideological bias of the reviewers is sometimes still very prominent. Although some scholars question its authenticity, in this article we will see that Musnad al-Imām Zaid ibn 'Alī is still open for further study and discussion. Differences in concepts and theories related to hadith between Sunni and Shi'i should not negate the existence of dialogue and discourse regarding the literature of the Shia. In general, the opportunity to study hadith in the Shia tradition is still very large and open.